2022
DOI: 10.1007/s12144-022-03823-3
|View full text |Cite
|
Sign up to set email alerts
|

Bending not breaking: coping among Filipino University students experiencing psychological distress during the Global Health Crisis

Abstract: and well-being (Deasy et al., 2014) and needs prevention and early intervention measures.Young people, particularly university students, are at greater risk for psychological distress in health emergencies (Bert et al., 2020) and traumatic events (Villani et al., 2021). Previous studies have reported that due to the COVID-19 pandemic, university students experienced mental health challenges (Mudenda, 2021;Cao et al., 2020) and high levels of psychological distress (Hughes et al., 2022;Akbar & Aisyawati, 2021).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 56 publications
(60 reference statements)
2
1
0
Order By: Relevance
“…Consistent with research conducted during the second year of the pandemic (Egcas et al., 2021), the current study indicates moderate well‐being among college student participants. Moreover, the present findings note high levels of psychological distress post‐lockdown, similar to an early COVID‐19 study conducted among Filipino university students (Serrano et al., 2022). Although the final multivariate models of the present study significantly predict both ends of the mental health spectrum, the results also suggest that socio‐ecological determinants have stronger explanatory power for mental well‐being (28.60% of variance) than psychological distress (9.83% of variance).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with research conducted during the second year of the pandemic (Egcas et al., 2021), the current study indicates moderate well‐being among college student participants. Moreover, the present findings note high levels of psychological distress post‐lockdown, similar to an early COVID‐19 study conducted among Filipino university students (Serrano et al., 2022). Although the final multivariate models of the present study significantly predict both ends of the mental health spectrum, the results also suggest that socio‐ecological determinants have stronger explanatory power for mental well‐being (28.60% of variance) than psychological distress (9.83% of variance).…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with research conducted during the second year of the pandemic (Egcas et al, 2021), the current study indicates moderate well-being among college student participants. Moreover, the present findings note high levels of psychological distress post-lockdown, similar to an early COVID-19 study conducted among Filipino university students (Serrano et al, 2022).…”
Section: Discussionsupporting
confidence: 88%
“…18 This cross-sectional survey revealed that the transition to online learning and work in the pandemic context may be a cause of distress among UP Manila students both from the perception of students and faculty members. Similar studies ascertained the distress situation among college students in the United States of America 19 , China 20 , Germany 21 , Belgium 22 , and the Philippines 23 have been published in the past two years.…”
Section: Discussionmentioning
confidence: 88%
“…This study did not consider academic stressors. 24 However, with regards the personal and family stressors, unclear boundaries between school and home, and family duties are among the factors that were perceived by both faculty and students as among those that are most common. An empirical study presents the importance of family relationships during pandemic periods when promoting preventive health behaviors of Filipino undergraduate students.…”
Section: Discussionmentioning
confidence: 99%
“…This is in addition to the preexisting sociocontextual challenges (e.g., lack of educational opportunities and technological resources, financial and employment issues, volatile familial conditions, and risk of dropping out from the university) that undergraduate students in the Philippines, a developing country in Southeast Asia, are already facing. The Philippines are one of the most heavily affected countries by the pandemic in Southeast Asia, and as Filipino students transition to the post pandemic phase of education, it is important to identify psychological resources that can be utilized to foster resilience, enhance well-being, and boost academic performance and success (Serrano & Reyes, 2022). Gratitude-based interventions offer promising results in enhancing university students’ well-being and buffering their mental health amid these psychosocial challenges (Datu, Buenconsejo, et al, 2022; Geier & Morris, 2022).…”
Section: Discussionmentioning
confidence: 99%